Top tips for IELTS academic (UCLES, 2009)
Top Tips for IELTS Academic gives you some essential advice ('tips') for each part of each of the four IELTS components (listening, Reading, Writing and Speaking). It is written by Cambridge ESOL, the organisation responsible for the production of the test,